The Effect of Demographic Variables on Teachers Decision to Quit or Stay on the Teaching Profession - Victor Mafone Alasa; Magdalene Ifeoma Ogbemudia (Universitas Sultan Ageng Tirtayasa, 2021)
Demographic variables as predicate of public secondary school teachers' decision to quit or study in the teaching profession using Akwa Ibom, Nigeria as a case study was the central focus of this study. In this study two demographic variables were considered namely gender and academic qualification. The study utilized a sample size of 50 teachers randomly sampled from five public secondary schools and the ex-post-facto design. The data was collected using the “Demographic variable and Teachers” Decision to Quit or Stay in Teaching Profession Questionnaire (DVTDQSTPQ). The data was analyzed with an independent t-test and the result at 0.05 level of significance showed that gender and academic qualification had no significant influence on teachers' decision to quit or stay in the teaching profession.